An Experimental Approach to Study the Effect of Welding Parameters on Mechanical Properties of 6061 Al Alloys by Friction Stir Welding - Bhushan, Bharat (Journal of Advanced Research in Mechanical Engineering and Technology, 2022)
Aluminium alloy 6061 is a structural material with exhibits good weldability, good damping capability and machine ability, is one of the most attractive material in applications of transportation and mobile electronics for effectively as a light weight. The structural application of Aluminium alloy involves welding and joining, which are difficult to weld using conventional welding processes. In 1991 a solid state joining process named Friction Stir Welding was developed and this technique has attracted considerable interest from the aerospace and automotive industries, since it is able to produce defect free joints particularly for light metals i.e. magnesium and aluminum alloy. In this investigation an attempt has been made to study the effect of friction stir welding parameters on mechanical and metallurgical properties of 6061 Al alloy. The selected material was welded using combination of different parameters i.e. tool rotational speed (1950 rpm and 3080 rpm), welding speed (20 mm/min and 40 mm/min) and tool shoulder diameter (18 mm and 20 mm). It has been observed that there was linear relationship between UTS and weld pitch. A maximum value of UTS i.e. 238.4 N/mm2 was obtained at 3080 rpm with 40 mm/min and 20 mm tool shoulder diameter. This study also revealed an inversely proportional relationship between grain size and weld pitch. The fine and equiaxed grains were obtained due to dynamic recrystallization at higher value of weld pitch. It was also observed that excessive heat generation and insufficient flow of plasticized material at higher values of tool rotational speed, leading to formation of defects which ultimately results in failure of weld joints between SZ and TMAZ. How to cite this article: Bhushan B. An Experimental Approach to Study the Effect of Welding Parameters on Mechanical Properties of 6061 Al Alloys by Friction Stir Welding. J Adv Res Mech Engi Tech 2022; 9(1&2): 1-5.